Pathoanatomic Findings Associated With Duty-Related Cardiac Death in US Firefighters: A Case-Control Study - Smith, Denise Louise; Haller, Jeannie M.; Korre, Maria; Fehling, Patricia C.; Sampani, Konstantina; Grossi Porto, Luiz Guilherme; Christophi, Costas A.; Kales, Stefanos N. (My University, 2018)
Background Sudden cardiac death accounts for the greatest proportion of duty-related deaths among US firefighters. Increased understanding of the pathoanatomic causes of sudden cardiac death and the risk associated with underlying cardiac pathologies is needed to develop evidence-based screening recommendations. Methods and Results Using autopsy data for duty-related firefighter fatalities occurring between 1999 and 2014, this retrospective case-control study compared cardiac findings of male firefighters aged 18 to 65 years who died on duty of cardiac-related causes with those who died of noncardiac trauma-related causes. Data from 276 cardiac cases and 351 noncardiac trauma controls were analyzed. Among cardiac cases, the most prevalent (82%) underlying pathoanatomic substrate was comorbid coronary heart disease and cardiomegaly/left ventricular hypertrophy. Cardiac cases had a higher prevalence of cardiomegaly (heart weight >450 g), left ventricular hypertrophy (left ventricular wall thickness ≥1.2 cm), and severe coronary artery stenosis (≥75%) than trauma controls (all P<0.001). In multivariate analyses, heart weight >450 g, coronary artery stenosis ≥75%, and evidence of a prior myocardial infarction were strong independent predictors of cardiac death, with odds ratios of 6.1 (95% confidence interval, 3.6-10.4), 9.3 (95% confidence interval, 5.3-16.1), and 6.2 (95% confidence interval, 3.4-11.3), respectively. Conclusions The majority of cardiac fatalities had evidence of both coronary heart disease and increased heart mass, and each condition was independently associated with a markedly elevated risk of cardiac death. Targeted screening for coronary heart disease, increased heart mass, and evidence of prior myocardial infarction should be considered to reduce duty-related cardiac deaths among firefighters.
Keywords: Autopsy; Cardiomegaly; Coronary heart disease; Firefighting; Left ventricular hypertrophy